Sex-Related Differences in Plasma Oxytocin Levels in Humans - Marazziti, Donatella (Clin Pract Epidemiol Ment Health, 2019)
BACKGROUND: Increasing evidence supports a key role of Oxytocin (OT) as a modulator of social relationships in mammals. OBJECTIVE: The aim of the present study was to investigate possible sex-related differences in plasma OT levels in human beings. METHODS: Forty-five healthy men and 45 women (mean age: 34.9 ± 6.2 years), were included in the study. Plasma preparation, peptide extraction and OT radioimmunoassay were carried out according to standardized methods. RESULTS: The results showed that OT plasma levels (pg / ml, mean ± SD) were significantly higher in women than in men (4.53 ± 1.18 vs 1.53 ± 1.19, p ˂ 0.001). CONCLUSIONS: The present finding demonstrates sex-related differences in plasma OT levels in humans. It is tempting to hypothesize that such differences might be related to behaviours, attitudes, as well as susceptibility to stress response, resilience and social emotions specific of women and men.